Inter-American development and the NAFTA : implications of liberalized trade for the Caribbean sugar industry. - CORONADO, Julie Lynn (1996)
Examines the treatment of the sugar industry in NAFTA, where Mexico, Canada and the US reduce barriers to trade among themselves while solidifying and strengthening existing protectionist policies towards the Dominican Republic.